Perbandingan Aktivitas Antioksidan Ekstrak Apel Hijau (Malus Domestica) Segar Dan Kering Dengan Metode Spektrofotometri - Youstiana Dwi Rusita; Ratih Purwasih (Poltekkes Kemenkes Surakarta, 2019)
Abstract: Green apples containing antioxidants substance that has beneficial effect in skin health. Green apples containing catechin, epicatechin, ploridzin, quercetin, ellergic acid and chlorogenic acid. One of food processing is hot drying, hot drying can influence bioactive substance in the food. The aim of this study is to measure antioxidant activity of fresh and dry green apple extract. Design of this study is experimental design, independent variable of this study is hot drying, and dependent variable of this study is antioxidant activity level. Extraction method using ultrasonic maseration, hot drying using oven. Antioxidant activity measuring using spectrophotometry method. IC50 level of fresh green apple extract is 31.26 ppm, IC50 of dry green apple extract is 52.36 ppm. IC50 level of fresh green apple extract are less than 50 ppm and IC50 level of dry green apple extract are more than 500 ppm. Conclusion of this study is fresh green apple extract has strong antioxidant activity and dry green apple extract has very strong antioxidant activity.